The development and validation of tau PET tracers: current status and future directions - Okamura, Nobuyuki (Clin Transl Imaging, 2018)
PURPOSE: To provide an overview on positron emission tomography (PET) imaging of tau pathology in Alzheimer’s disease (AD) and other neurodegenerative disorders. RESULTS: Different classes of tau tracers such as flortaucipir, THK5317, and PBB3 have been developed and utilized in previous clinical studies. In AD, the topographical distribution of tracer binding follows the known distribution of neurofibrillary tangles and is closely associated with neurodegeneration as well as the clinical phenotype of dementia. Significant retention of tracers has also been observed in the frequent site of the 4-repeat (4R) tau isoform deposits in non-AD tauopathies, such as in progressive supranuclear palsy. However, in vitro binding studies indicate that most tau tracers are less sensitive to straight tau filaments, in contrast to their high binding affinity to paired helical filaments of tau (PHF-tau). The first-generation of tau tracers shows off-target binding in the basal ganglia, midbrain, thalamus, choroid plexus, and venous sinus. Off-target binding of THK5351 to monoamine oxidase B (MAO-B) has been observed in disease-associated brain regions linked to neurodegeneration and is associated with astrogliosis in areas of misfolded protein accumulation. The second generation of tau tracers, such as [(18)F]MK-6240, is highly selective to PHF-tau with little off-target binding and have enabled the reliable assessment of PHF-tau burden in aging and AD. CONCLUSIONS: Tau PET tracers have enabled in vivo quantification of PHF-tau burden in human brains. Tau PET can help in understanding the underlying cause of dementia symptoms, and in patient selection for clinical trials of anti-dementia therapies.